Model Fundraising Dakwah di Masjid Perkotaan - Mauludi, Muh Syahril Sidik Ibrahim; Ali Nurdin; Agoes Moh. Moefad; Shobikhul Qisom; Moch Herma Musyanto; Ahmad Faiz Khudlari Thoha (Journal of Islamic Management, 2025)
Mosques play a pivotal role in the socio-economic development of Muslim communities, particularly through effective fundraising management. Mosque fundraising is not only a tool for collecting donations but also a means to achieve economic empowerment and financial sustainability for religious and social programs. This study analyzes mosque fundraising strategies in Surabaya, focusing on community-based, partnership-based, digital, and institutional models. It examines how Masjid Rahmat Kembang Kuning, Masjid Cheng Hoo, and Masjid Al Falah implement diverse donation management approaches, ensure financial transparency, and build trust among congregants. Utilizing a qualitative methodology with a Grounded Theory approach, data were collected through in-depth interviews, direct observations, and document analysis involving mosque administrators, donors, and active congregants. Findings reveal that community- based fundraising initiatives like the Warung Dzuhur program and Haul Mbah Karimah effectively foster congregational engagement through collective participation. Partnership-based fundraising, exemplified by Masjid Cheng Hoo, secures financial stability via corporate sponsorships and foundation collaborations. Digital fundraising expands donation channels through QRIS, social media, and online payment systems, enhancing transparency and donor confidence. The study concludes that innovative and participatory fundraising strategies grounded in Islamic management principles strengthen mosque financial sustainability, enhance congregational trust, and empower mosques as independent and socially impactful institutions. The findings offer a strategic framework for mosques to optimize fundraising while maintaining Sharia-compliant financial governance and promoting community empowerment.